2021
DOI: 10.1016/j.psj.2021.101343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a yeast-derived product on growth performance, antioxidant capacity, and immune function of broilers

Abstract: Yeast culture plus enzymatically hydrolyzed yeast cell wall ( YC-EHY ) contains crude protein, mannan-oligosaccharide, β-glucan and yeast culture. This study was carried out to explore the effects of dietary YC-EHY at different levels on growth performance, antioxidant capacity, and immune function of broiler chickens. A total of 320 one-day-age male broiler chicks were allocated into 4 groups and were fed with a basal diet supplemented with 0 mg/kg (the control group), 50 mg/kg, 100 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
4
19
1
Order By: Relevance
“…Our previous study has showed that dietary YH addition linearly and quadratically increased (linear and quadratic, p<0.05) the body weight gain and gain-to-feed ratio during the starter (1 to 21 d), growth (22 to 42 d), and overall (1 to 42 d) periods of broilers [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study has showed that dietary YH addition linearly and quadratically increased (linear and quadratic, p<0.05) the body weight gain and gain-to-feed ratio during the starter (1 to 21 d), growth (22 to 42 d), and overall (1 to 42 d) periods of broilers [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research suggested that dietary supplemented with brewer's yeast hydrolysate had beneficial effects on growth performance in finishing pigs [7]. Similarly, our previous study had found that YH supplementation could improve the body weight gain but decrease the gain to feed ratio during the starter, grower and overall period of broilers [20]. The growth performance might be affected by many factors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Yeast culture (YC) is a unique micro-ecological product that is composed of yeast biomass (including some residual viable cells, dead cells, and yeast-cell-wall fragments), fermentation metabolites, and the residual growth medium [ 14 ]. YC contains a rich variety of biologically active substances, including proteins, small peptides, oligosaccharides, vitamins, minerals, enzymes, and numerous ‘unknown growth factors’, which can all exert beneficial nutritional and health effects on animals.…”
Section: Introductionmentioning
confidence: 99%